Tumor‐derived exosomes in the PD‐1/PD‐L1 axis: Significant regulators as well as promising clinical targets. Issue 6 (4th December 2020) - Liang, Benhui; Hu, Ximin; Ding, Yinghe; Liu, Mujun
Abstract: Programmed cell death‐1 (PD‐1) is a negative coreceptor mainly expressed on the surface of activated T cells. The binding of PD‐1 to its ligand PD‐L1 significantly induces non‐reactivity of T cells to maintain the balance of autoimmunity and immune tolerance. It is reported that tumor cells highly express PD‐L1 to restrict cellular immune response, which is one of the most important mechanisms for tumor to mediate immune escape. Cancer immunotherapy targeting PD‐1/PD‐L1 has achieved remarkable success so far. Tumor‐derived exosomes (TEXs) are lipid bilayer vesicles released by tumor cells in an endosome‐dependent manner, mediating communication between tumor cells and adjacent cells in the tumor microenvironment. Through signals transmitted by TEXs, tumor can alter the biological characteristics of these cells to promote tumor growth and metastasis. Recent studies have demonstrated that TEXs not only carry tumor‐derived PD‐L1, but are also closely related to PD‐1/PD‐L1 expression on target cells. The primary focus of this review will be on how TEXs regulate the PD‐1/PD‐L1 axis to promote tumor progression, and the promising clinical applications targeting TEXs and exosomal PD‐L1. Abstract : Tumor‐derived exosomes (TEXs) are lipid bilayer vesicles released by tumor cells, mediating communication between tumor cells and adjacent cells in the tumor microenvironment. This review mainly focuses on how TEXs regulate the programmed cell death‐1 (PD‐1)/ligand of PD‐1 (PD‐L1) axis to promote tumor progression, and the promising clinical applications targeting TEXs and exosomal PD‐L1.